Efektivitas Sclerotherapy Sebagai Metode Non-Invasif Untuk Pengobatan Hemoroid : Literature Review - Wahdini, Ridha (Jurnal Keperawatan Muhammadiyah, 2025)
Introduction: Hemorrhoids are one of the most common anorectal diseases, with prevalence increasing with age. While various management and treatment options are available, sclerotherapy offers a minimally invasive alternative. Sclerotherapy has emerged as a promising non-surgical method, the lack of comprehensive clinical guidelines and the diverse research findings on its effectiveness create a need for a systematic review. This literature review aims to comprehensively analyze the existing evidence regarding the effectiveness of sclerotherapy as a non-invasive treatment for hemorrhoids. Methods: This study is a literature review analyzing 10 journals that meet the inclusion criteria. Data sources were obtained from scientific databases such as PubMed, Mendeley, and ScienceDirect using relevant keywords and were published within the last five years. A comprehensive literature search was conducted following the Preferred Reporting Items for Systematic Reviews (PRISMA) 2020 flow diagram. Results: Analysis of the 10 reviewed journals indicates that sclerotherapy is effective in reducing hemorrhoid symptoms, particularly bleeding and pain. Several studies also reported lower recurrence rates and faster recovery following sclerotherapy treatment. Conclusion: This systematic review highlights the safety and effectiveness of sclerotherapy in the treatment of hemorrhoids, with comparable success rates and fewer complications than other conservative or surgical methods. Further research is needed to optimize sclerotherapy techniques and evaluate its long-term outcomes